2008
DOI: 10.1620/tjem.216.297
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Earlier Menarche and Low Parity as Independent Risk Factors for Gynecologic Cancers in Japanese: A Case-Control Study

Abstract: During recent decades, the incidence of gynecologic cancers, i.e., cancers of the cervix, endometrium and ovary, has increased in Japan. However, risk factors of gynecologic cancers have not been fully clarified in Japan. To investigate common and site-specific risk factors among gynecologic cancers, we conducted a hospital-based case-control study. The cases, i.e., 151 cervical, 103 endometrial and 141 ovarian cancer cases and the controls (n = 2016) were selected from female patients aged 30 and over, who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 37 publications
4
39
2
2
Order By: Relevance
“…[22][23][24] The presence of cervical cancer in a first degree relative increases the risk 1.5-2.3 times 8 and the risk increases up to 4.8 times in twins. 8,24 In our study, 4.6% of the women (Table 2), and in the study by Twinn et al 46.0% of women stated that "multiple births" increased the risk of cervical cancer.…”
Section: Level Of Knowledgesupporting
confidence: 56%
See 1 more Smart Citation
“…[22][23][24] The presence of cervical cancer in a first degree relative increases the risk 1.5-2.3 times 8 and the risk increases up to 4.8 times in twins. 8,24 In our study, 4.6% of the women (Table 2), and in the study by Twinn et al 46.0% of women stated that "multiple births" increased the risk of cervical cancer.…”
Section: Level Of Knowledgesupporting
confidence: 56%
“…4 Many factors have been proposed as causes of cervical cancer including early onset of sexual activity or early marriage, multiple sexual partners, unprotected sexual intercourse, a high-risk sexual partner, smoking, history of sexually transmitted diseases, prolonged use of oral contraceptives, high parity, family history and low socio-economic status. [5][6][7][8][9][10] Cancer control aims at reducing the burden and suffering from cancer, to prevent exposure to risk factors, and to enable early detection, effective treatment and relief from symptoms and pain in incurable advanced cases.…”
mentioning
confidence: 99%
“…Studies carried out elsewhere (9), as well as a few case-control studies in Japan (8,20,23,25) have reported similar inverse associations.…”
Section: Discussionmentioning
confidence: 70%
“…These associations may differ across populations and ethnic groups, and could partially explain differences in incidence rates across countries. Risk factors for epithelial ovarian cancer among Japanese women have been examined in one prospective cohort study (14)(15)(16) besides ours (17), and in several case-control studies (8,(18)(19)(20)(21)(22)(23)(24)(25), with inconsistent results.…”
Section: Introductionmentioning
confidence: 96%
“…The procedure used in this survey has already been described previously (Minami and Tateno 2003;Fujita et al 2008;Kawai et al 2012Kawai et al , 2013Nishino et al 2014). The purpose of the survey was explained on the cover page of the questionnaire.…”
Section: Data Collectionmentioning
confidence: 99%